2013
DOI: 10.1111/fcp.12053
|View full text |Cite
|
Sign up to set email alerts
|

Antihepatitis B therapy: a review of current medications and novel small molecule inhibitors

Abstract: There are approximately 350 million hepatitis B virus (HBV) carriers worldwide. Chronic HBV infection increases the risk of liver cirrhosis and hepatocellular carcinoma. To date, two classes of antiviral drugs have been approved by the Food and Drug Administration for the treatment of hepatitis B, immunomodulators (interferon [IFN]-α and pegylated-interferon [PEG-IFN]-α) and nucleos(t)ide analogs (lamivudine, telbivudine, adefovir, tenofovir [TDF], and entecavir [ETV]). Of these, ETV, TDF, and PEG-IFN-α are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 163 publications
(257 reference statements)
0
14
0
Order By: Relevance
“…It was reported that AS‐IV exerts potent anti‐HBV activity. AS‐IV not only could inhibit the HBsAg expression and the HBeAg secretion in HeG 2 2.2.15 cells, but also reduce the level of DHBsAg in DHBV‐infected ducks .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 97%
“…It was reported that AS‐IV exerts potent anti‐HBV activity. AS‐IV not only could inhibit the HBsAg expression and the HBeAg secretion in HeG 2 2.2.15 cells, but also reduce the level of DHBsAg in DHBV‐infected ducks .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 97%
“…The number of HBV-related targets used for antiviral interventions is very limited. Currently available anti-HBV drugs are (i) the nucleoside/nucleotide analogs (entecavir, lamivudine, adefovir dipivoxil, tenofovir and telbivudine) that target only the reverse transcription; and (ii) versions of interferon alpha (including alpha-2b interferon and pegylated alpha-2a interferon) that are beneficial only to a subset of infected individuals (Asselah et al, 2007; Lam et al, 2011; Lok et al, 2007; Papatheodoridis and Hadziyannis, 2004; Papatheodoridis et al, 2012; Qiu et al, 2013). For comparison, unlike HBV, anti-HIV therapies work against four different kinds of virus-specific targets.…”
Section: Introductionmentioning
confidence: 99%
“…PCR amplification was performed using a similar method to the literature we described previously. 50 Briefly, the human colorectal cell lines (LOVO for wild-type p53 and SW620 for mutant p53 ) were cultured at 37 °C in Ham's F12K liquid medium supplemented with 10% fetal calf serum (FCS). The harvested cells (about10 7 ) were used to extract genomic DNA using the TaKaRa MiniBEST Universal Genomic DNA Extraction Kit Ver.5.0 (Takara Biotechnology).…”
Section: Methodsmentioning
confidence: 99%